anonymous
  • anonymous
Solve this system of equations using the addition method? x-y=6 -3y=x+22 Solve this system of equations using the addition method? x-y=6 -3y=x+22 @Mathematics
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
y=-7 x=13
anonymous
  • anonymous
that true?
amistre64
  • amistre64
scale the 1st by -3

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

amistre64
  • amistre64
-3x +3y = -18 -3y = x+22 ---------------- -3x = x+4 -4x = 4
anonymous
  • anonymous
how do you get x+4
amistre64
  • amistre64
by using the "addition" method ... you add the 2 equations together after you modify one of them by a scalar
amistre64
  • amistre64
a scalar just means some number that you multiply the whole equation by to scale it up or down to something that you can use
anonymous
  • anonymous
o so i just substitute it
amistre64
  • amistre64
well, substitution will work as well; but this is a new method for you to learn so that you have many ways you can attack a problem to get to a solution
amistre64
  • amistre64
this "addition" method is also commonly refered to as "elimination" since the goal is to eliminate one of the variables
anonymous
  • anonymous
o ok thank you u make it sound easier to solve
anonymous
  • anonymous
so if i were to have -8x+3y=-5 and 8x-2y=6 i would add the _8x and the 8x to get zero then 3-2y to get y and -5+6 to get 1 right
amistre64
  • amistre64
practice helps :) the steps are pretty much like this: x - y = 6 ; (1) -3y = x + 22 ; (2) given 2 equations lets multiply one of them by a "n"umber to scale it. the easiest one would be the first one to me n(x - y = 6) ; (1) -3y = x + 22 ; (2) nx - ny = 6n ; (1) -3y = x + 22 ; (2) now what does "n" have to be to get rid of the -3y? id say n = -3 will work -3x - -3y = 6(-3) ; (1) -3y = x + 22 ; (2) -3x +3y = -18 ; (1) -3y = x + 22 ; (2) now we can add the equations together: -3x +3y = -18 ; (1) -3y = x + 22 ; (2) ---------------------- -3x = x + 4 ; (3) and solve the new equation (3) for the remaining variable
amistre64
  • amistre64
if they give you: -8x+3y =-5 8x-2y = 6 then yes the x parts are already set up for elimintion, just add the 2 equations together
anonymous
  • anonymous
ok thank u sooo much i would give u thousands of medals if i could
amistre64
  • amistre64
youre welcome, and good luck ;)

Looking for something else?

Not the answer you are looking for? Search for more explanations.